(untitled) (Philological Studies, 2019)
Followers’ needs and expectations have the moderating effects on the effectiveness of various types of leader’s behavior or style. They vary from one culture to another. Their consideration is very important as work organizations become increasingly international and different leadership’s styles are efficient in different cultures. Assuming that leaders can identify which style of leadership is appropriate for certain culture, they have to assure that they behave in a way which is interpreted as consistent with that style.